Urban Quality in Growing Cities. The Case of Rzeszów in Poland - Stachura Ewa Joanna; Jagiełło Magdalena; Martyka Anna (Real Estate Management and Valuation)
The economic transformation, which started in 1990 in Poland, opened the possibility to produce and offer flats and apartments in the free market. Since 1990, developers have constructed about 4 million flats, increasing housing resources by more than 30%. The building quality (technologies and materials implemented) improved significantly compared to structures from the pre-transformation period. New investments have been located mainly in cities and city outskirts, complementing the existing development in medium or low development density or open areas, rarely followed by new infrastructure: roads, public transportation, recreational areas and services. These elements define urban quality, an essential indicator of the quality of life. Increasing the density of development threatens the city’s urban structure and worsens the urban quality and residents’ satisfaction. Such phenomena also hamper achieving sustainable development goals. For this study, one of the most dynamically growing cities, Rzeszow, representing a group of medium-sized cities in Poland, was selected and investigated to assess the urban quality of districts/neighborhoods where new housing complexes appeared after 2010. After identifying and describing the essential elements that provide urban quality in cities in Poland and the factors shaping them, the paper presents the survey results that reveal the quality of the neighborhood system, including residential development constructed after 2010.